2010
DOI: 10.1007/s00127-010-0208-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of physical and sedentary activities in the development of depressive symptoms in early adolescence

Abstract: Low levels of vigorous exercise and high levels of sedentary activities (boys only) constituted independent risk factors for the development of a high level of depressive symptoms in a 1-year study of young adolescents. This knowledge should be considered by policy makers, preventative services, and health-care professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
119
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(141 citation statements)
references
References 47 publications
14
119
0
8
Order By: Relevance
“…However, because psychomotor retardation and loss of energy are among the symptoms of MDD, it is essential to adjust for previous MDD when examining sedentary activity's contribution to MDD, which has been investigated only to a limited extent. 21,49 Further, in many of these prospective studies, self-reports of inactivity and depression have been applied that may inflate their relationship on a prospective basis, due to the common methods that are employed. Moreover, it is essential to adjust for lack of MVPA when estimating the effects of sedentariness because MVPA and sedentary activity are negatively correlated.…”
Section: No Prospective Relation Between Sedentary Activity and Symptmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because psychomotor retardation and loss of energy are among the symptoms of MDD, it is essential to adjust for previous MDD when examining sedentary activity's contribution to MDD, which has been investigated only to a limited extent. 21,49 Further, in many of these prospective studies, self-reports of inactivity and depression have been applied that may inflate their relationship on a prospective basis, due to the common methods that are employed. Moreover, it is essential to adjust for lack of MVPA when estimating the effects of sedentariness because MVPA and sedentary activity are negatively correlated.…”
Section: No Prospective Relation Between Sedentary Activity and Symptmentioning
confidence: 99%
“…A substantial amount of research has focused on MVPA; however, several studies have revealed that sedentary behavior, not necessarily MVPA, might predict depression. 20,21 Thus, we will investigate the extent to which time spent in sedentary activities predicts symptoms of MDD over and above the effects of MVPA. Fourth, there is considerable comorbidity between depression and other psychiatric disorders in children, 22,23 and these disorders might be related to PA, confounding the relationship between depression and PA as a result.…”
mentioning
confidence: 99%
“…2 Weights to account for non-response bias were derived using stepwise logistic regression techniques using data which were available from previous Health Surveys for England.…”
mentioning
confidence: 99%
“…Seemingly lower cardiovascular fitness is not a risk factor for bipolar depression (or mania) and may not be a risk factor for females. 2 It is not stated whether consideration was given to psychiatric disorders apart from depression (e.g. anxiety disorders) and this leaves uncertainty as to whether lower cardiovascular fitness at age 18 is only a risk factor for non-bipolar depression in males.…”
mentioning
confidence: 99%
“…A depresszió és a szorongás kezelésében is felhasználják a testmozgás kedvező hatását (Sund, Larsson és Wichstrøm, 2011;Salmon, 2001;Mather, Rodriguez, Guthrie, McHarg, Reid és McMurdo, 2002). A hangulatra gyakorolt pozitív befolyása is régóta ismert (Berger, 1996;Morgan, 1997 a "verseny-és sikerorientáció", a "külső megerősítés" a "fittség és egészség + sportolói viselkedés" valamint a "hedonoista" faktorokkal voltak jellemezhetőek a fiatalok motivációja (Bollok, Takacs, Kalmar és Dobay, 2011).…”
Section: Egészségre Gyakorolt Rövid Távú Hatásokunclassified